Phenomenology: Exploring Women’s Experiences of First Time IUD Insertion - Fevriasanty, Fransiska Imavike; Lyneham, Joy; McCauley, Kay (Department of Nursing, Faculty of Medicine, Diponegoro University, 2013)
Purpose: This study aims to explore Indonesian women’s experiences of first-time IUD insertion.Method: This study using phenomenological approach. Three Javanese women who lived in Malang Indonesia were interviewed using an unstructured process and the women’s native language was utilized. Soon after the interview, transcripts were translated from Indonesian into English, and phenomenological analysis of data was used.Result: The results revealed one major and three minor themes and identify embarrassment as the major contribution to women’s feelings of powerlessness. These feelings emerged because women experienced a lack of privacy during the insertion procedure. Women are vulnerable especially when there is no support received while facing a stressful medical procedure.Conclusion: Women need assistance from the health staff in order to deal with this traumatic experience. This improvement will includes the enhancement of clinic staff communication skills, the enrichment of health practice in providing better service and the upgrading of health policy that focuses on nurses/ doctors’ attitudes to give women-centered care.